Dampak Covid-19 dan Penggunaan Financial Technologi di Industri Perbankan Jambi - Julianti ES, Eka; Fitra A, Rian; Taufik, Haviz (Jurnal Akuntansi & Keuangan Unja, 2024)
Focus of this research is the impact of the use of financial technology during the Covid-19 pandemic. Fintech is one of the financial services that provides convenience in transactions. The purpose of this study is to see the impact of fintech and Covid-19 on the Jambi banking industry. This type of research is descriptive quantitative research. The data sources used in the study are secondary data and primary data. The variables analyzed in this study are financial ratios consisting of Capital Adequacy Ratio, Loan to Deposit Ratio, Return on Assets, Operating Costs to Operating Income BOPO, and Non Performing Loans. Hypothesis testing is carried out using different tests, namely the paired sample T-Test and the Wilcoxon signed rank test. The results of the hypothesis test show that there are differences and relationships between the Capital Adequacy Ratio (CAR), Loan to Deposit Ratio (LDR), and Operating Costs to Operating Income (BOPO) with the use of Financial Technology during the Covid-19 pandemic, while the variables, Return on Assets (ROA) and Non Performing Loans (NPL) have no difference.